2019
DOI: 10.1088/1361-6528/ab261f
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous intercalation of Ga and In bilayers during plasma-assisted molecular beam epitaxy growth of GaN on graphene on SiC

Abstract: The formation of a self-limited metallic bilayer is reported during the growth of GaN by plasma-assisted molecular beam epitaxy on graphene on (0001) SiC. Depending on growth conditions, this layer may consist of either Ga or In, which gets intercalated between graphene and the SiC surface. Diffusion of metal atoms is eased by steps at SiC surface and N plasma induced defects in the graphene layer. Energetically favorable wetting of the (0001) SiC surface by Ga or In is tentatively assigned to the breaking of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Although the intercalation of H, Ga, Sn, and In underneath the buffer layer of EMLG has been demonstrated by others using non-engineered EMLG samples, [17,32,63,75,92] the engineering of defects (i.e., multi-atomic discontinuities in the graphene) can significantly promote intercalation. [31,68,91] The engineered defects in these previous works were of relatively high density, with a separation of ≈300-700 nm, [31] or directly observable in the C 1s spectra as judged with a lab-based XPS. [68] Our work differs from these previous efforts in that the patterning of the substrate does not necessarily need to be in such high density in order to greatly facilitate intercalation.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Although the intercalation of H, Ga, Sn, and In underneath the buffer layer of EMLG has been demonstrated by others using non-engineered EMLG samples, [17,32,63,75,92] the engineering of defects (i.e., multi-atomic discontinuities in the graphene) can significantly promote intercalation. [31,68,91] The engineered defects in these previous works were of relatively high density, with a separation of ≈300-700 nm, [31] or directly observable in the C 1s spectra as judged with a lab-based XPS. [68] Our work differs from these previous efforts in that the patterning of the substrate does not necessarily need to be in such high density in order to greatly facilitate intercalation.…”
Section: Resultsmentioning
confidence: 97%
“…Our patterned lines have a dimension of 2 × 2600 µm 2 , and are separated by 200 µm, in stark contrast with previous efforts. [31,68,91] Our "defect-free" areas are at least three orders of magnitude greater, and thus, have the benefit of large defect-free areas in which devices could be fabricated. Furthermore, we have demonstrated that the rate of Mg-intercalation increases proportionally with the increase in graphene edge length.…”
Section: Resultsmentioning
confidence: 99%
“…The bright line visible above SiC corresponds to the intercalation of a 2 monolayer (ML) thick pure Ga layer under graphene. It was recently established that the formation of this metallic bilayer is mediated by metal diffusion from the defective graphene regions on SiC steps and further promoted during growth by the additional defects created by N-plasma in graphene [14].…”
Section: Resultsmentioning
confidence: 99%
“…Also, exposure to N plasma leads to homogeneization of graphene doping and strain state. [14]. In this context, it appears necessary to investigate the interplay between metallic/N fluxes and graphene during the first stages of the epitaxial growth of GaN by MBE.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated in the case of graphene, exposure to N plasma produces electronic and structural defects[23]. As the mica surface is terminated by a layer of Si/Al atoms tetrahedrally coordinated to O, and due to high chemical reactivity of N with Si, it is expected that N ions from the plasma can react with the surface.…”
mentioning
confidence: 99%